2022
DOI: 10.36565/jab.v11i1.501
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Massage Effleurage dan Teknik Relaksasi terhadap Tingkat Nyeri Punggung Ibu Hamil Trimester III di Puskesmas Kenali Besar Kota Jambi

Abstract: Back pain is one of the most frequently reported complaints by pregnant women, varying from 50% to 70%, even 8% of them result in severe disability. Back pain is described as one of the minor disorders in pregnancy and is one of the causes of the incidence of cesarean delivery. From the initial survey, it was found that 4 out of 6 third trimester pregnant women had back pain complaints. The purpose of this study was to determine the effectiveness of Massage Effleurage and Relaxation Techniques on back pain in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…While in the control group, the p-value of 0.317 was greater than α (0.05), then HA was rejected and it can be concluded that there is no difference between the scale of back pain of III trimester pregnant women in the pre-test and posttest in the control group. This is in line with previous research conducted by (Suryani et al, 2022) with the research title "The effectiveness of massage effleurage and relaxation techniques on the level of back pain of third trimester pregnant women at the Puskesmas Kenali Besar Jambi City" this study they used the Wilcoxon test to show that p-value = 0.000 which means there is an effect of giving effleurage massage on reducing back pain for III trimester pregnant women. and also in line with research conducted by ( Dian Agustriryani with the research title "The effect of warm compresses on the intensity of back pain in third trimester pregnant women at PMB D South Jakarta City in 2022" the results of this study using the Wilcoxon test obtained significant results of 0.000 smaller than the significant level of 5% (p-value = 0.000 < 0.05), then the conclusion is that Ha is accepted which means there is an effect of warm compresses on back pain in III trimester pregnant women.…”
Section: The Effectiveness Of the Combination Of Effleurage Massage A...supporting
confidence: 87%
See 1 more Smart Citation
“…While in the control group, the p-value of 0.317 was greater than α (0.05), then HA was rejected and it can be concluded that there is no difference between the scale of back pain of III trimester pregnant women in the pre-test and posttest in the control group. This is in line with previous research conducted by (Suryani et al, 2022) with the research title "The effectiveness of massage effleurage and relaxation techniques on the level of back pain of third trimester pregnant women at the Puskesmas Kenali Besar Jambi City" this study they used the Wilcoxon test to show that p-value = 0.000 which means there is an effect of giving effleurage massage on reducing back pain for III trimester pregnant women. and also in line with research conducted by ( Dian Agustriryani with the research title "The effect of warm compresses on the intensity of back pain in third trimester pregnant women at PMB D South Jakarta City in 2022" the results of this study using the Wilcoxon test obtained significant results of 0.000 smaller than the significant level of 5% (p-value = 0.000 < 0.05), then the conclusion is that Ha is accepted which means there is an effect of warm compresses on back pain in III trimester pregnant women.…”
Section: The Effectiveness Of the Combination Of Effleurage Massage A...supporting
confidence: 87%
“…This heat response is used for pain reduction therapy. The therapeutic effect of applying warm compresses will be able to reduce muscle spasms and reduce joint bone stiffness (Suryani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%